1975
DOI: 10.1136/bmj.1.5949.67
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of inhibition of prostaglandin biosynthesis by analgesics to asthma attacks in aspirin-sensitive patients.

Abstract: SummaryEleven patients with asthma and aspirin hypersensitivity have been challenged with eight non-steroidal antiinflammatory drugs. Each drug was given by mouth in at least three different doses and the patients' symptoms and peak expiratory flow (PEF) rates were observed over a three-hour period. Indomethacin 5 mg caused bronchoconstriction in all patients. Therapeutic doses of mefenamic or flufenamic acid caused bronchoconstriction in most patients. Phenylbutazone 200-400 mg induced a moderate fall in PEF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
208
1
10

Year Published

1976
1976
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(225 citation statements)
references
References 11 publications
6
208
1
10
Order By: Relevance
“…2,3 The underlying mechanisms of aspirin-intolerance appear to be related to inhibition of cyclo-oxygenase with subsequent release of leukotrienes and other mediators. 4 Our previous study, using the leukotriene D 4 receptor antagonist montelukast, confirmed the evidence that leukotrienes play an important role in the development of nasal polyps in patients with aspirin-intolerant asthma. 5 Trials of desensitisation, using aspirin, have been reported in patients with aspirin-intolerant asthma.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…2,3 The underlying mechanisms of aspirin-intolerance appear to be related to inhibition of cyclo-oxygenase with subsequent release of leukotrienes and other mediators. 4 Our previous study, using the leukotriene D 4 receptor antagonist montelukast, confirmed the evidence that leukotrienes play an important role in the development of nasal polyps in patients with aspirin-intolerant asthma. 5 Trials of desensitisation, using aspirin, have been reported in patients with aspirin-intolerant asthma.…”
Section: Introductionsupporting
confidence: 61%
“…This is thought to cause an exacerbation of asthma and the formation of nasal polyps. 4 Intranasal therapy with lysine-aspirin has been reported to be effective in both aspirin-sensitive and aspirin-tolerant nasal polyps. 9,14 -16 Nucera et al 15 showed, in an open study, that the relapse rates of nasal polyps after medical or surgical polypectomy were significantly lower than those for a non-randomised control group, in patients receiving a low (sub-desensitising) dose of lysine-aspirin once weekly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a clear correlation between the potency of a drug to inhibit COX in vitro and its ability to precipitate a clinical reaction. We presented these results at an international conference in London in 1974 and published them in British Medical Journal in 1975 [7], expanding the results to other NSAIDs in the following two years. These results were confirmed by several other laboratories and led to the development of the cyclooxygenase theory of AIA.…”
Section: Mechanisms Of the Diseasementioning
confidence: 99%
“…Other analgesic and/or anti-inflammatory agents, such as mefenamic acid, indomethacin, paracetamol and phenylbutazone may also produce asthmatic episodes in man (Samter & Beers, 1968;Smith, 1971;Szczeklik, Gryglewski & Czerniawska-Mysik, 1975;Delaney, 1975). Paradoxically, most of these agents counteract bronchoconstriction induced in experimental animals by slow reacting substance of anaphylaxis (SRS-A) or bradykinin (Berry & Collier, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Samter & Beers (1968) have postulated that altered responses of peripheral chemoreceptors initiate a series of reflexes in which mild analgesics act as agonists rather than antagonists. Lately, inhibition of biosynthesis of prostaglandins by aspirin and other mild analgesics has been associated with their ability to induce asthmatic episodes (Szczeklik et al, 1975).…”
Section: Introductionmentioning
confidence: 99%